1998
DOI: 10.1086/311604
|View full text |Cite
|
Sign up to set email alerts
|

The X-Ray Expansion of the Supernova Remnant Cassiopeia A

Abstract: We present the first X-ray expansion measurements of the young, bright supernova remnant Cas A. We have acquired a deep (232 ks) ROSAT high-resolution image of Cas A that is compared with archival images of similar quality taken 17 yr earlier with the Einstein Observatory. The average expansion rate between the two epochs is found to be yr Ϫ1, twice as fast as the expansion of the bright radio ring and two-thirds as fast 0.20% ‫ע‬ 0.01% as the ensemble of optical fast-moving knots. This argues that we are obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 23 publications
10
34
0
Order By: Relevance
“…These knot measurements confirmed that the X-ray Doppler expansion rate agrees with the X-ray proper motion rate, ∼ 0.2 % yr −1 on average (Koralesky et al 1998;Vink, et al 1998;DeLaney et al 2004). Perhaps somewhat surprisingly, the expansion rate of the FS is about the same as the X-ray ejecta (DeLaney & Rudnick 2003;Patnaude & Fesen 2009).…”
Section: Core-collapse X-ray Observationssupporting
confidence: 72%
“…These knot measurements confirmed that the X-ray Doppler expansion rate agrees with the X-ray proper motion rate, ∼ 0.2 % yr −1 on average (Koralesky et al 1998;Vink, et al 1998;DeLaney et al 2004). Perhaps somewhat surprisingly, the expansion rate of the FS is about the same as the X-ray ejecta (DeLaney & Rudnick 2003;Patnaude & Fesen 2009).…”
Section: Core-collapse X-ray Observationssupporting
confidence: 72%
“…This provides further insight into the well-known large-scale asymmetries in Cas A's expansion (Tuffs 1986;Reed et al 1995;Koralesky et al 1998). The reverse shock is found to be offset to the northwest by ∼0Ј .22 (∼15% of the ring radius) from the center of the forward shock.…”
Section: Cas A's Dynamical Statementioning
confidence: 57%
“…Our data are within two dashed lines. Other data shown as stars are responsible for the Cas A SNR at 350 yr (Koralesky et al, 1998;Vink et al, 1998), the Kepler's SNR at 400 yr (Katsuda et al, 2008;Vink, 2008), the Tycho's SNR at 430 (Hughes, 2000), SN1006 at 1000 yr (Moffett et al, 1993), and the Cygnus Loop at 10,000 yr (Blair et al, 2005). The solid line is the bestfit Power-law function representing the data points of five other SNRs.…”
Section: Discussionmentioning
confidence: 96%